ANALISIS PERIZINAN LINGKUNGAN MENURUT UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (Lex Jurnalica, 2021)
This scientific writing is entitled Analysis of Environmental Permits According to Law Number 32 of 2009 concerning Environmental Protection and Management. This paper uses a normative analysis method and a statutory approach. The quality of the living environment is decreasing, the quality of life for humans and other living creatures, so it is necessary to protect and manage the environment. Environmental Licensing plays an important role in efforts to protect and manage the Environment. This paper will further discuss the meaning, type, and scope of the Environmental Licensing system and the factors causing the revocation of Environmental Permits, and Procedures and Requirements for Issuing Environmental Permits.